2023
DOI: 10.1111/jns.12543
|View full text |Cite
|
Sign up to set email alerts
|

Charcot–Marie–Toothneuropathies: Current gene therapy advances and the route toward translation

Abstract: Charcot–Marie–Tooth (CMT) neuropathies are a group of genetically and phenotypically heterogeneous disorders that predominantly affect the peripheral nervous system. Unraveling the genetic and molecular mechanisms, as well as the cellular effects of CMT mutations, has facilitated the development of promising gene therapy approaches. Proposed gene therapy treatments for CMTs include virally or non‐virally mediated gene replacement, addition, silencing, modification, and editing of genetic material. For most CMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 244 publications
0
13
0
Order By: Relevance
“…Gene replacement strategies have been tested at preclinical level for both demyelinating and axonal CMTs, where the genes of interest have been expressed using AAV9 [ 85 , 88 ]. Following systemic delivery or via intracerebroventricular (i.c.v.)…”
Section: Inherited Peripheral Neuropathies (Ipns)mentioning
confidence: 99%
“…Gene replacement strategies have been tested at preclinical level for both demyelinating and axonal CMTs, where the genes of interest have been expressed using AAV9 [ 85 , 88 ]. Following systemic delivery or via intracerebroventricular (i.c.v.)…”
Section: Inherited Peripheral Neuropathies (Ipns)mentioning
confidence: 99%
“…From the PubMed search of animal gene therapy studies in CMT, 27 articles were most recently identified in July 2023 ( 10 ), with the most relevant studies with references listed ( Table 1 ). Targeted gene therapy approaches include utilization of viral delivery by LV ( n = 4), AAV ( n = 9), CRISPR-Cas9 ( n = 2), squalene nanoparticles ( n = 1), and antisense oligonucleotides ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…No therapeutics that directly target CMT1A have proven clinical effects on CMT1A. As summarized in recent reviews 9 , 10 , various therapeutics currently developed include indirect methods to increase viability of Schwann cells and/or neurons and direct approaches to decrease PMP22 protein expression. Preclinical studies in rodent models suggested that soluble neuregulin-1 54 , 55 , AAV1-mediated delivery of neurotrophin-3 (NT3) 56 , P2X7 receptor inhibition 57 , shRNA 15 , AAV-mediated expression of miRNA 16 , and antisense oligonucleotides targeting PMP22 7 could improve CMT1A pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, no therapeutic interventions are available whose effects are clinically confirmed for CMT or CMT1A 6 , 9 , 10 . Primary management includes physiotherapy and occupational therapy and in some cases non-steroidal anti-inflammatory drugs (NSAIDs) or antidepressants to manage pain 6 10 , 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation